A New Diterpenoid From The Steam of Hibiscus mutabilis Linn. - Ma , Yin-Hai; Li , Yin-Ke; Yang, Hai-Ying; Dai, Yun; Li, Gan-Peng (Asian Journal of Chemistry, 2010)
Phytochemical investigation of the stem of Hibiscus mutabilis Linn. led to the isolation and identification of a new diterpenoid named Hibtherin A. The structure was elucidated by analysis of spectroscopic data.